The Correct Answer Is B- Above Par
Answer:
140 x 180
Step-by-step explanation:
To find the measure of the unknown angle in a straight angle ABC, you can use the equation A = A + A. This equation is derived from the Pythagorean theorem, which relates the legs of a right triangle to the length of the hypotenuse.
To find the measure of the unknown angle in a straight angle ABC, you can use the equation A = A + A. This equation is derived from the Pythagorean theorem, which relates the legs of a right triangle to the length of the hypotenuse. In a straight angle, the two legs are equal, so the equation simplifies to A = 2A. Therefore, the measure of the unknown angle is twice the measure of one of the legs
x = 3y - 2
Which equivalent equation could be used?
y = 3(4y + 5) - 2
x = 3(4y + 5) - 2
x = 4(3y - 2) + 5
4y + 5 = 3y - 2
Answer:
The choice two
Step-by-step explanation:
Answer: y = -x + 5 and y = -x - 7 (see attached graph)
Step-by-step explanation:
y =
= 9(x + 1)⁻¹
Use the product rule to find the derivative
a = 9 a' = 0
b = (x + 1)⁻¹ b' = -(x + 1)⁻²
ab' + a'b
= 9[-(x + 1)⁻²] + 0[(x + 1)⁻¹ ]
=
Set the derivative equal to the desired slope of -1 to solve for x
-1 =
-(x + 1)² = -9
(x + 1)² = 9
√(x + 1)² = √9
x + 1 = +/- 3
x + 1 = 3 x + 1 = -3
x = 2 x = -4
Plug those values into the original equation to solve for y:
y =
=
= 3
(2, 3)
y =
=
= -3
(-4, -3)
Next, plug in the given slope (-1) and the coordinates above into the Point-Slope formula y - y₁ = m(x - x₁) to find the equations:
m = -1, (x₁ y₁) = (2, 3) m = -1, (x₁ y₁) = (-4, -3)
y - 3 = -1(x - 2) y + 3 = -1(x + 4)
y - 3 = -x + 2 y + 3 = -x - 4
y = -x + 5 y = -x - 7
Answer:
First tangent line:
Second tangent line:
Notice: slope of -1 means that both are equal to -1, so